The effect of hormone therapy on the level of depression and quality of life in women in perimenopausal age, living in the countryside - Makara-Studzińska, Marta; Wdowiak, Artur; Bakalczuk, Grzegorz; Bakalczuk, Szymon (Menopause Review/Przegląd Menopauzalny, 2009)
Aim of the study: The aim of this study is to compare the level and intensity of depression symptoms and other symptoms visible in perimenopausal period in women living on the rural areas, who take hormone therapy (HT) and women who don’t take this therapy. Material and methods: 91 women, country habitants, in age of 45-55 were tested in two groups. First group – a clinical group-consisted of women who take hormone therapy (HT), and the second group-a control group-consisted of women who don’t take this therapy. In the test was used the anonymous self-developed questionnaire, including questions concerning the occurrence of the menopausal symptoms, treatment with hormone and conclusions therapy and Beck Depression Inventory. Among 91 tested women, 39 don’t take hormone therapy and 52 do or did. The statistical analysis was conducted with help of the chi-square test. Results and conclusions: An essential difference was found in frequency of the depression symptoms occurrence between the clinical group and the control group. Only 13.5% of women taking the HRT suffered from some depression symptoms, while the frequency of the depression symptoms in group of woman who didn’t take this therapy was 59%. On the basis of those results, it can be said that HRT has an influence on the reduction of some ailments connected with menopausal period such as: anxiety, weakness and headaches.